Establishment of Extra-Pancreatic Source of Insulin in Liver of Poultry (Gallus domesticus) - Dutta, Sajal Kumar; Das, Partha (Indian Journal of Veterinary Anatomy, 2013)
The crude insulin from poultry pancreas was extracted and identified by SDS-PAGE.The insulin antibody was raised in rabbit and purified by protein affinity chromatography.The liver and pancreas were explored for possible source of insulin by immunohistochemistry and immunoflorosence techniques. Immuno positive cells were revealed in the islets of pancreas and in the hepatocytes of the liver against anti poultry insulin antibody raised in rabbit.These results suggested liver as a possible source of insulin.